Assessing the deposition and canopy penetration of nozzles with different spray qualities in an oat (Avena sativa L.) canopy - Ferguson, J. Connor; Chechetto, Rodolfo G. [UNESP]; Hewitt, Andrew J.; Chauhan, Bhagirath S.; Adkins, Steve W.; Kruger, Greg R.; O'Donnell, Chris C. (Elsevier B.V., 2016)
Consistent spray coverage that is evenly distributed throughout the canopy is necessary to control pest populations that can negatively affect yield. As applicators are switching to Coarser spray quality nozzles to reduce risk and liability of pesticide spray drift, concerns about efficacy loss are growing. Previous research has indicated that small droplets are the most effective at penetrating through crop canopies, but newer nozzle technologies have improved the effectiveness of larger droplet or Coarser sprays. Research was conducted to assess the canopy penetration of nozzles that produce Coarse, Very-Coarse and Extremely-Coarse spray qualities compared to nozzles that produce Fine and Medium spray qualities. Kromekote collectors were positioned in four configurations in an oat (Avena sativa L.) var. 'Yarran' (AusWest Seeds, Forbes, NSW, Australia) crop to quantify the coverage and droplet number densities (droplets cm(-2)) across three application carrier volume rates: 50, 75 and 100 L ha(-1). Applications were made in the field in 30 cm tall, tillering oats, with collectors arranged in a randomised complete block design with three replications. The entire study was repeated on the following day. Results showed that droplet number densities were inversely related to the droplet size produced by the nozzles, yet coverage was increased more by application volume rate than droplet size. Thus, both spray drift reduction and improved canopy penetration can be achieved with proper nozzle selection and operation parameters for the control of agronomic pests. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Spray quality; Application volume rate; Coverage; Droplet number density; Nozzle; Spray drift; Pesticide efficacy